2024
DOI: 10.1038/s41467-024-45954-0
|View full text |Cite
|
Sign up to set email alerts
|

Annexins—a family of proteins with distinctive tastes for cell signaling and membrane dynamics

Volker Gerke,
Felicity N. E. Gavins,
Michael Geisow
et al.

Abstract: Annexins are cytosolic proteins with conserved three-dimensional structures that bind acidic phospholipids in cellular membranes at elevated Ca2+ levels. Through this they act as Ca2+-regulated membrane binding modules that organize membrane lipids, facilitating cellular membrane transport but also displaying extracellular activities. Recent discoveries highlight annexins as sensors and regulators of cellular and organismal stress, controlling inflammatory reactions in mammals, environmental stress in plants, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 151 publications
1
4
0
Order By: Relevance
“…The large family of annexin proteins show a very heterogeneous cell- and tissue-specific expression pattern. 17 Here, we identified annexin A4 as specifically enriched in tumor cells of clear cell renal cell carcinoma (ccRCC), in line with previous studies reporting increased protein levels of ANXA4. 23,39 Given the context- and cell-type dependent role of individual annexins, a comprehensive functional characterization of ANXA4 in ccRCC was to date missing.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The large family of annexin proteins show a very heterogeneous cell- and tissue-specific expression pattern. 17 Here, we identified annexin A4 as specifically enriched in tumor cells of clear cell renal cell carcinoma (ccRCC), in line with previous studies reporting increased protein levels of ANXA4. 23,39 Given the context- and cell-type dependent role of individual annexins, a comprehensive functional characterization of ANXA4 in ccRCC was to date missing.…”
Section: Discussionsupporting
confidence: 89%
“…23,39 Given the context- and cell-type dependent role of individual annexins, a comprehensive functional characterization of ANXA4 in ccRCC was to date missing. 17 In this study, we demonstrated that ANXA4 exhibits distinct subcellular localization patterns related to separate biological function such as membrane repair as well as modulation of transcriptional signatures employing in vitro, in silico and in situ approaches.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…MtAnn1 is a cytosolic phospholipid-and Ca 2+ -interacting protein of the annexin family 13 , viewed as dynamic regulators that associate with membranes when intracellular Ca 2+ levels change 15,16 . Annexin family members are involved in the regulation of ion transport, modulation of cytoplasmic Ca 2+ signals and ROS signalling in diverse abiotic or biotic responses [71][72][73][74][75] .…”
Section: Role Of Mtann1 In Modulating Cell-and Stage-specific Symbiot...mentioning
confidence: 99%
“…The rhizobia-and AM-induced MtAnn1 13 and MtAnn2 14 genes, which encode cytosolic Ca 2+ binding annexins that can bind to membranes to modulate a variety of Ca 2+ -regulated processes (e.g. ion conductance, exocytosis/endocytosis) 15,16 , are potential players in this process.…”
Section: Introductionmentioning
confidence: 99%